RANCANG BANGUN SISTEM INFORMASI PRESENSI KARYAWAN PADA PT INFINITE BUSINESS SYNERGY DI JAKARTA - Setiawan, Setiawan; Ash Shiddieqy, Muhammad Hasby (JURNAL LENTERA ICT, 2021)
The recording of employees' daily attendance still uses manual input. With these conditions, HRD staff find  it  difficult  to control employees  when the hours are in, whether the employee is really in the office. The next obstacle is recording attendance written  on  paper,  it  will  be  vulnerable  to  lost  data  damaged  and  difficulty  in recapitulating it. This will lead to uncontrolled employees. In the research phase carried out is collecting  field  data by observation,  and  analyzing  system requirements.  By looking at the needs, the system is made web-based, the next stage is to design, build a database with MYSQL, design the user interface, build a system using the Laravel framework, and create and test programs. Based on the results of the system test, the design of the employee attendance information system at PT Infinite Business Synergy in Jakarta can facilitate the parties with an interest in this final project (in terms of authors, companies, and in education) to obtain the information and benefits needed, to become a solution in increasing discipline for employees as well as making it easier to record, control and report because it is easily accessible via web media.Keywords: Framework, Design, Employees, Presence